2021
DOI: 10.1186/s12879-021-06894-y
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a hospital-associated cluster of COVID-19 in Malaysia

Abstract: Background Hospitals are vulnerable to COVID-19 outbreaks. Intrahospital transmission of the disease is a threat to the healthcare systems as it increases morbidity and mortality among patients. It is imperative to deepen our understanding of transmission events in hospital-associated cases of COVID-19 for timely implementation of infection prevention and control measures in the hospital in avoiding future outbreaks. We examined the use of epidemiological case investigation combined with whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Large-scale SARS-CoV-2 sequencing programs throughout the pandemic have allowed researchers to explore the role of viral genomics and different variants of the virus. However, whilst genomic epidemiology has been used in a number of studies to understand viral transmission in settings such as hospitals [14][15][16][17], long-term care facilities [18][19][20][21][22], and army barracks [23,24], well-powered studies of patient outcomes with high numbers of cases currently remain limited [25][26][27][28][29][30][31]. One of the largest studies looking at large-scale effects of viral genomics on patient outcomes are papers from the Hospital Onset COVID-19 Infections (HOCI) study in the UK [25,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale SARS-CoV-2 sequencing programs throughout the pandemic have allowed researchers to explore the role of viral genomics and different variants of the virus. However, whilst genomic epidemiology has been used in a number of studies to understand viral transmission in settings such as hospitals [14][15][16][17], long-term care facilities [18][19][20][21][22], and army barracks [23,24], well-powered studies of patient outcomes with high numbers of cases currently remain limited [25][26][27][28][29][30][31]. One of the largest studies looking at large-scale effects of viral genomics on patient outcomes are papers from the Hospital Onset COVID-19 Infections (HOCI) study in the UK [25,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These outbreaks can lead to increase in workload due to reduced number of HCWs and increased number of patients, which put a strain on health care services. 3 Although, in Malaysia, up to 70% of SARS-CoV-2 infections among HCWs were community-acquired, there is still a need to identify SARS-CoV-2 transmitted through patients-HCWs or HCWs-HCWs cross-infections. 4 Therefore, we aimed to explore the factors associated with workplace transmission among HCWs who contracted coronavirus disease (COVID-19).…”
Section: Introductionmentioning
confidence: 99%
“…The researches showed that the epidemiological characteristics (such as the spatial, temporal and population distributions) and clinical characteristics (such as clinical manifestations, disease severity) of COVID-19 among medical personnel in different regions, periods, and medical institutions were different, [4][5][6][7][8][9] based on the variation of SARS CoV-2 virus, as well as the changes in medical system and prevention and control strategies, population density and mobility, medical resources, COVID-19 vaccination and antibody levels of population etc. 10 Hospitals are vulnerable to COVID-19 outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial outbreak of the COVID-19 in Wuhan at the end of December 2019, in the past three years, outbreaks of nosocomial COVID-19 infections have occurred in many countries, such as Malaysia, Spain, Switzerland, Germany, Italy, and Vietnam. [4][5][6][7][8][9][10][11] However, the epidemiological and clinical characteristics of these outbreaks are not all the same, their morbidity and case fatality rates and the scale of the outbreaks varies. In China, the government has adopted stringent COVID-19 prevention and control measures until November 2022, with low morbidity and mortality, and few large-scale COVID-19 outbreaks in hospitals.…”
Section: Introductionmentioning
confidence: 99%